Improving Language Skills of 5-6 Years Old Children with Storytelling Method and Picture Word Card Media - Cahyati, Ulya; Karta, I Wayan; Astawa, I Made Suwasa; Fahruddin (Journal for Lesson and Learning Studies, 2022)
Language is a very important thing, through language children can express thoughts and knowledge when interacting with other people. This study aims to analyze the effect of partially and simultaneously the application of the storytelling method and picture word card media on the language skills of children aged 5-6 years. This research belongs to the type of experimental research with a one-group pretest-posttest design. The population in this study amounted to 45 children. Sampling was done by purposive sampling method, and the number of samples obtained was 15 early childhood children. Data collection in the study was carried out using structured observation methods, document analysis, and applying multiple regression analysis to test hypotheses. The research instrument used is in the form of an observation sheet. Data analysis techniques used are normality test, linearity test and hypothesis testing. The results showed that there is a positive influence on the application of picture word cards on the language skills of children aged 5-6 years. The results of Hypothesis show that there is a positive influence on the application of the storytelling method and picture word cards together on the language skills of children aged 5-6 years. Based on these results, it can be concluded that there is a positive effect of the application of storytelling methods and picture word card media on the language skills of children aged 5-6 years.